Comparative efficacy and safety of Cilnidipine and Amlodipine in the management of hypertension (Ibrahim Cardiac Medical Journal, 2025)
Background & objective: Hypertensive patients with coronary artery disease and diabetes mellitus usually benefit  from selective antihypertensive medications like calcium channel blockers (CCBs). Of the dihydropyridine (DHP) CCBs,  amlodipine has an excellent pharmacokinetic and pharmacodynamic profile. The only drawback of amlodipine is that it  causes pedal oedema leading to drug discontinuation in many cases. The new generation CCB, cilnidipine has  demonstrated equal efficacy in controlling blood pressure, but its adverse effect as is observed in amlodipine has not  been widely tested. The present study was, therefore, designed to make a comparative evaluation of cilnidipine and  amlodipine in the management of blood pressure in hypertensive individuals.  Patients & Methods: The present non-randomized clinical trial was conducted in the private practices of renowned  cardiologists and specialists in internal medicine in Chittagong Metropolitan City over a period of four years, from  January 2020 to December 2023. A total of 496 hypertensive patients of both sexes were consecutively enrolled in the  study. Among them, 455 patients-246 in the Amlodipine group and 209 in the Clinidipine group completed the two  scheduled follow-up visits within six months of the intervention (the study endpoint) and were subsequently included  in the final analysis. The study drugs were considered effective if 80% of the subjects in the study experienced control  of blood pressure (systolic blood pressure < 140 mmHg and/or diastolic blood pressure < 90 mmHg) after 6 months  of intervention with the study drugs. The study drugs were termed safe if they did not cause impairment of renal,  neuro, and cardiac functions significantly during the study period. Pedal oedema was assessed by clinical method over  the medial malleolus of both legs.  Result: The cilnidipine and amlodipine groups were comparable regarding age and sex. However, obesity and diabetes  were more prevalent in the amlodipine group, while smokers were more frequent in the cilnidipine group. Mean systolic  and diastolic blood pressures were slightly lower in the cilnidipine group. Fasting blood sugar levels were similar, and  dyslipidemia was common in both groups. The comparative evaluation of cilnidipine and amlodipine in the  management of systemic hypertension revealed significant differences in heir efficacy and safety profiles. Both  medications effectively reduced blood pressure, with a greater mean reduction in systolic blood pressure being  observed in the amlodipine group compared to the cilnidipine group (19.9% vs. 15.6%, p < 0.001). However, the  incidence of adverse effects, particularly pedal edema, was notably higher in the amlodipine group (11% vs. 4.8%, p  = 0.016), indicating a preference for cilnidipine among hypertensive patients concerned about tolerability. Despite  these differences in side effects and blood pressure control, the overall efficacy in achieving target blood pressure  levels (SBP < 140 mmHg and DBP < 90 mmHg) was comparable between the two groups, as evidenced by the high  control rates of 87% in the amlodipine group and 88.5% in the cilnidipine group (p = 0.622).  Conclusion: The study concluded that both cilnidipine and amlodipine are equally effective in reducing blood pressure  in hypertensive individuals. However, cilnidipine is less likely to cause pedal oedema than amlodipine. This advantage  of cilnidipine makes it a preferred antihypertensive drug over amlodipine. Ibrahim Card Med J 2024; 14(1): 19-27